A facile and scalable self-assembly strategy to prepare two-dimensional nanoplates: a precursor for a Li-rich layered cathode material Li1.2Mn0.54Ni0.13Co0.13O2 with high capacity and rate performance. (1st May 2017) - Dai, Dongmei; Yan, Dongwei; Li, Bao; Chang, Kun; Chang, Zhaorong; Tang, Hongwei; Li, Yanping; Zhou, Shaoxiong
Graphical abstract: Highlights: A synthesis parameters are optimized to obtain 2D nanoplate of M(OH)2 . Li-rich layered oxide delivers a capacity of 323.8 mAh g −1 without surface decoration or doping. The formation mechanism of nanoplate is proposed to be a self-assembly process. The strategy is facile and scalable in synthesis of 2D precursor for high performance cathode. Abstract: Li-rich layered oxide is one of the most promising cathode materials for high-energy-density Li-ion batteries (LIBs). The composition, structure and morphology of precursors have significant influence on the electrochemical performance of the final cathode material. The capacity and initial coulombic efficiency of Li1.2 Mn0.54 Ni0.13 Co0.13 O2 can be simultaneously improved by sintering a nanoplate precursor with Li2 CO3 in our previous work. Herein, the morphology and the formation mechanism of such nanoplate are investigated through a designed orthogonal tests. The optimal concentration of transition metal ions, 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (HEPES) and polyvinyl pyrrolidone (PVP) are 0.1, 0.031 and 0.004 g mL −1, respectively. The as-prepared Li1.2 Mn0.54 Ni0.13 Co0.13 O2 from optimal nanoplate demonstrate an improved discharge capacity (323.8 mAh g −1 at 20 mA g −1 ), initial coulombic efficiency (81.3%), and rate capability (195.8 mAh g −1 at 3C). This new precursor architecture opens a promising avenue for the development of high-performances cathode materials of LIBs.